Analisis Balok dan Kolom Struktur Beton (Studi kasus café di Jl. Manunggal, Desa Gedongombo, Kecamatan Semanding, Kabupaten Tuban) - Dandy Nugroho; Akhmad Andi Saputra; Dedi Agung Cahyono (Wahana Teknik, 2020)
Structural design is an important element in the construction of a building in order to produce a strong, safe and economical building. Overall, the building structure consists of two parts, namely the upper structure (in the form of floors, beams, columns, walls and roofs) and the lower structure (in the form of foundations and sloof beams). Columns and beams are the structure of the building frame, therefore it is very important, so that dimensions and use of reinforcement that are safe and economical must be planned. Changing the function of an office building into a café building needs to recalculate the beam and column structure. In the load regulation, the live load value of café buildings is greater than that of office buildings, so it is necessary to recalculate the dimensions of the beam and column structures so that they are able to withstand the existing loads in the cafe building. This study analyzes the beams and columns of concrete structures using a load-bearing frame system with tools from the STAADPro program according to SNI-2847-2013 regarding structural concrete requirements for buildings. The conclusion of this research is that the beam section uses a size of 300 x200mm and the column section uses a size of 300 x 300mm. Column section uses 8 Ø12 bending reinforcement, the support beam uses 2 Ø12 upper reinforcement 3 Ø12 lower reinforcement, field beam uses 7 Ø12 upper reinforcement 4 Ø12. Keywords: Analysis, Beams, Columns, Concrete, Structure.